Absorption and Metabolism Characteristics of Rutin in Caco-2 Cells - Xiaofang Zhang; Jinhui Song; Xiaopeng Shi; Shan Miao; Yan Li; Aidong Wen (The Scientific World Journal)
The intestinal absorption and metabolism characteristics of the potentially beneficial polyphenol rutin were studied by measuring the intracellular accumulation and transport of rutin into Caco-2 cells with the sensitive and reliable analytical method of HPLC-coupled tandem mass spectrometry. Rutin and glucuronidated rutin were absorbed differently by the basolateral and apical membranes, and rutin showed differential permeability through the apical and basolateral sides. Approximately 33% of the rutin was metabolized to glucuronidated rutin, and the intracellular concentration of glucuronidated rutin was much lower than that of parent rutin. P-glycoprotein and multidrug-resistant proteins 2 and 3 were involved in the transmembrane transport and intracellular accumulation of rutin by Caco-2 cells. These results suggest that a specific transport system mediates rutin movement across the apical membrane in Caco-2 cells and that metabolic enzymes are important for this process.